Patient handling in the healthcare sector : a guide for risk management with MAPO methodology (movement and assistance of hospital patients) /: a guide for risk management with MAPO methodology (movement and assistance of hospital patients). (2014) - Menoni, Olga; Battevi, Natale; Cairoli, Silvia
No abstract available